Current stress optimization control strategy of the buck topology with the variable frequency/amplitude mode - Li, Ning; Li, Zhuang; Cao, Yujie; Wei, Deng; Xiao, Zihan; Zhang, Yan (Frontiers in Energy Research, 2023)
The Buck circuit is a common topology in DC-DC converter. The existing control strategies have the advantages of short modulation time and high dynamic performance, but they also have the disadvantages of poor active modulation of the working mode of the converter and large current stress. In response to the above problems, an improved frequency/amplitude modulation control strategy is proposed in this paper. The relationship between the output power and the peak inductor current in three modes, namely, Discontinuous Conduction Mode Critical Conduction Mode (CRM) and Continuous Conduction Mode is derived. The precise control strategy of the inductor peak current is introduced based on the traditional voltage loop control strategy to realize the free control of the system working mode and reduce the current stress during the working process. Finally, the experimental platforms of 100V/12V and 220/80V are established respectively. The experimental results show that the flexible switching circuit operating mode in the full load range can be realized under the new control method. In the 100/12V experimental platform, the current stress of the switch tube is optimized by at least 10.7%, and the average system efficiency is improved by 2.21%, with the same main circuit parameters.